Association of IL6 and IL10 gene promotor polymorphisms with susceptibility to acute necrotizing encephalopathy - Hoshino, Ai; Takahashi, Naoto; Oka, Akira; Mizuguchi, Masashi (Frontiers in Neuroscience, 2023)
Objective: Acute necrotizing encephalopathy (ANE) is a severe complication of infectious diseases affecting the brain and systemic organs. The main pathogenesis is cytokine storm, in which interleukin-6 (IL-6) and interleukin-10 (IL-10) are candidates for key cytokines. To further elucidate their roles in the etiology and pathogenesis of ANE, we studied polymorphisms in the promotor regions of the IL6 and IL10 genes by genetic and functional analyses.We first conducted a case-control association study of four IL6 and three IL10 polymorphisms. We genotyped 31 Japanese ANE cases and compared the results with those of approximately 200 Japanese controls. For the two polymorphisms showing a possible association, we next studied whether the polymorphisms alter the production of IL-6 or IL-10 by lymphoblasts upon phorbol 12-myristate 13-acetate (PMA) stimulation.The frequencies of IL6 rs1800796G allele and IL10 rs1800871/rs1800872 CC/CC diplotype were significantly higher in ANE cases than in controls. The IL10 CC/CC diplotype was associated with low IL-10 production, whereas the IL6 GG genotype was not associated with IL-6 production.Conclusion: IL10 rs1800871/rs1800872 CC/CC diplotype may predispose Japanese children to ANE by altering IL-10 production in the early phase of infection. Etio-pathogenetic significance of IL6 rs1800796G remains to be elucidated.